Executive summary: evaluating the evidence base to support the inclusion of infants and children from birth to 24 mo of age in the Dietary Guidelines for Americans—"the B-24 Project". Issue 3 (5th February 2014) - Raiten, Daniel J; Raghavan, Ramkripa; Porter, Alexandra; Obbagy, Julie E; Spahn, Joanne M
ABSTRACT: The Dietary Guidelines for Americans (DGA) are the cornerstone of US government efforts to promote health and prevent disease through diet and nutrition. The DGA currently provides guidelines for ages ≥2 y. In an effort to determine the strength of the evidence to support the inclusion of infants and children from birth to age 24 mo, the partner agencies led by the Department of Health and Human Services Office of Disease Prevention and Health Promotion and the USDA Center for Nutrition Program and Policy initiated the project entitled "Evaluating the evidence base to support the inclusion of infants and children from birth to 24 months of age in the Dietary Guidelines for Americans —the B-24 Project." This project represents the first step in the process of applying systematic reviews to the process of deciding whether the evidence is sufficient to include this age group in future editions of the DGA. This supplement includes the B-24 Executive Summary, which describes the B-24 Project and the deliberations of the 4 working groups during the process of developing priority topics for the systematic review, and a research agenda to address the critical gaps. Also included in this supplement issue is an article on the Nutrition Evidence Library methodology for developing systematic review questions and articles from the invited content presenters at the B-24 Prime meeting.